(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
Prison misconduct is violation of prison rules through which prisoners are governed to regulate their behavior by the prison authorities. The aim of present study was to examine relationship between criminogenic cognitions of prisoners and prison misconduct in the Punjab, Pakistan. Conducting a survey of 363 adult convicted prisoners from the Punjab prisons, data were collected by using structured questionnaires and analyzed in SPSS-26. The study concluded that the relationship between criminogenic cognitions of prisoners and prison misconduct was found strong and positive. On the basis of these findings, criminogenic cognitions—dynamic risk factors of the prisoners may be assessed by the prison authorities at the time of prisoners’ entry into custody which would help them in an appropriate and scientifically based classification. This classification would clearly distinguish the high, medium, and low risk offenders and their probability in engaging in future criminal activities inside the prisons and after their transition into society. Policies based on these conclusions derived from the classification would reduce prison misconduct as well as enhance the chances of institutional adjustment which would provide a conducive environment for prison management to run rehabilitation programs for prisoners. Based on the findings of this study, it is recommended that prison authorities in Punjab, Pakistan, incorporate assessments of criminogenic cognitions as part of the intake process for convicted prisoners.